2013
DOI: 10.1016/j.ccr.2013.08.023
|View full text |Cite
|
Sign up to set email alerts
|

DNp73 Exerts Function in Metastasis Initiation by Disconnecting the Inhibitory Role of EPLIN on IGF1R-AKT/STAT3 Signaling

Abstract: Dissemination of cancer cells from primary tumors is the key event in metastasis, but specific determinants are widely unknown. Here, we show that DNp73, an inhibitor of the p53 tumor suppressor family, drives migration and invasion of nonmetastatic melanoma cells. Knockdown of endogenous DNp73 reduces this behavior in highly metastatic cell lines. Tumor xenografts expressing DNp73 show a higher ability to invade and metastasize, while growth remains unaffected. DNp73 facilitates an EMT-like phenotype with los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 42 publications
2
97
0
Order By: Relevance
“…These DNp73 functions are in agreement with recent data indicating that DNp73 drives migration and invasion of non-metastatic melanoma cells facilitating the epithelialmesenchymal transition phenotype of these cells. 55 It has become increasingly clear that tumor vessel abnormalities contribute to create a microenvironment that facilitates tumor progression. Therefore, it is highly relevant to identify novel molecules involved in angiogenesis and to integrate them in the molecular networks that orchestrate vascular morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These DNp73 functions are in agreement with recent data indicating that DNp73 drives migration and invasion of non-metastatic melanoma cells facilitating the epithelialmesenchymal transition phenotype of these cells. 55 It has become increasingly clear that tumor vessel abnormalities contribute to create a microenvironment that facilitates tumor progression. Therefore, it is highly relevant to identify novel molecules involved in angiogenesis and to integrate them in the molecular networks that orchestrate vascular morphogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have provided substantial evidence that DNp73 bestows chemoresistance by decreasing intracellular drug accumulation through upregulation of the ABC transporters A2, A5, and B1 (2,3). Moreover, we recently demonstrated that the DNp73 variant DEx2/3p73 causes dramatic increases in cancer malignancy via promoting the transition from an epithelial to a highly motile mesenchymal (EMT) phenotype, leading to increased invasiveness and metastases formation in xenograft mouse models (4). DNp73-mediated acquisition of mesenchymal properties involves interference with wild-type TAp73-dependent transactivation of LIMA1/EPLIN that consecutively fosters activation of the IGF1R-AKT-Slug signaling and downregulation of E-cadherin.…”
Section: Introductionmentioning
confidence: 99%
“…H1299 and A549 lung cancer cells obtained from the ATCC, and HEK293T (BioCat, Heidelberg, Germany) are tested and authenticated by short tandem repeat analysis (in 2015). Cells were cultured as described previously (4). For inhibitor studies, cells were exposed to IGF1R Inhibitor II (Merck; 30 mmol/L) or antisense-oligonucleotide ASO116 gapmer (4, 7).…”
Section: Cell Culture and Antisense Oligonucleotide Transfectionmentioning
confidence: 99%
“…In melanoma, both isoforms of p63 (TAp63 and DeltaNp63) negatively regulate apoptosis through ameliorating expression of Bcl-2 through translocation to the mitochondria and preventing nuclear p53 stabilization in response to genotoxic stress [60]. In case of p73, DeltaNp73 is considered as an oncoprotein since the expression of DeltaNp73 is linked to progression and metastasis in melanoma [61,62]. In contrast, TAp73 plays a role of tumour suppressive role in melanoma.…”
Section: Preventing Other Mechanisms From Inactivating P53mentioning
confidence: 99%